Personality Traits to Develop Entrepreneurship Skills of College Students: A Case study of Student Entrepreneurial Program - Sukirno,; Wahidin Septa Zahran,; Rousdy Safari Tamba,; Suparman, (Technium Social Sciences Journal, 2020)
In the current millennium era, all countries hope to encourage the birth of young entrepreneurs to drive the national economy, including Indonesia. One of the efforts made by the government is the Program Mahasiswa Wirausaha (PMW) or Student Entrepreneurial Program which is also a startup priority program of the Higher Education delegated to universities. This program was born because of the big number of educated unemployed people in Indonesia. This research aims at answering the questions on what personality traits needed by young startups in order that students can run their business professionally and what efforts should be taken to improve their personality in order to succeed to be professional entrepreneurs. It is a qualitative research with a phenomenological approach. Semi structured interviews were applied to students who have got the block-grant for operating the startup. The research proved that to be able to succeed in operating business and maintaining the sustainability, students’ knowledge on personality traits to develop entrepreneurship skills is demanded. For future research, it is recommended to conduct a study on the students’ startups with different approach.